PERSEPSI PESERTA DIKLAT TERHADAP PENGGUNAAN METODE PEMBELAJARAN OLEH NARASUMBER PELATIHAN PENDIDIK PAUD DI SKB LIMA PULUH KOTA - Danthy Meillya Sari (Universitas Negeri Padang, 2014)
Learning methods used by the narasumber training early childhood educators which is affecting the continuity of training participants in the learning process and learning methods are the ways of doing things or presenting, explaining, giving examples, and providing the training to participants of that training to achieve the identified objectives/ goals. Learning methods used by the narasumber training early childhood educators are communicative method, discussion method, demonstration method, and method of work trips. This type of research is descriptive quantitative research, the subject of the research is the training participants early childhood educators in SKB Lima Puluh Kota. The result of this research shows that the narasumber has implemented communicative method, discussion method, demonstration method, work trips method of learning according to most of the training participants.